TELA’AH KITAB RIJAL AL-HADIS TAHZIB AL-KAMAL FI ASMAI AL-RIJAL KARYA AL-MIZZI - Ibnu Ahmad Saefudin; Umayah Umayah; Ahmad Faqih Hasim (Jurnal Studi Hadis Nusantara, 2019)
ABSTRAKHadῑś al-Rijal science is the science that explains the biography of narrators. Study book Tahżῑb al-Kamāl Fῑ Asmā al-Rijāl the work of al-Mizzi, a book that explains the biography of narrators contained in kutub al-Sitta. This study examines the book by digging the information contained in it. This paper describes how al-Mizzi wrote down the names of transmitters contained in the book. The method is a qualitative method or methods that describe the data, the results will be analyzed so that it can be concluded.Keywords : Scripture and tradition rijal